PENINGKATAN KINERJA WADUK KEDUNGOMBO DENGAN MENGEMBALIKAN KAPASITAS TAMPUNGANNYA - bramantyo herawanto; Suripin Suripin; Dyah Ari Wulandari (Racic : Rab Construction Research, 2023)
In every reservoir plan, the volume of dead storage provided is always taken into account to accommodate sediment entering the reservoir during the service life of the reservoir. Several studies on reservoir sedimentation show that 70% of reservoirs have sedimentation problems so the effective life of the reservoir will end before the design life is reached. The rate of sediment entering the reservoir will settle in the dead reservoir and the effective reservoir which will affect the performance of the reservoir. Therefore, it is necessary to take measures to improve the performance of the reservoir, one way is to restore its effective reservoir. Based on the results of bathymetry measurements of the Kedungombo Reservoir from 1989 to 2017, the sediment rate was 1.954 million m3/year. From the analysis of sediment distribution, the dead reservoir of the Kedungombo Reservoir at an elevation of +65.00 will be filled in 2089. The effective reservoir in 2089 at a normal water level of +90.00 of 527.71 million m3 has decreased by 106.89 million m3 from the initial effective reservoir is 634.6 million m3. To improve reservoir performance by restoring its effective reservoir, the Kedungombo Reservoir requires an elevation of the overflow or normal water level as high as 2.26 m with an inundation area of ​​48.72 million m2. Keywords: Sediment Distribution, Storage Capacity, Reservoir Performance, Kedungombo Reservoir